Analyzing the Needs of General Education Teachers to Teach Students with Visual Impairment in Inclusive Settings - Ashraf, Samina; Jahan, Musarrat; Fida, Farah; Fatima, Iqra (Pakistan Journal of Humanities and Social Sciences, 2023)
The main objective of the current study was to analyze the needs of general education teachers to teach SWVI in inclusive settings and explore the differences based on gender and locality.The quantitative research approach was used to frame the study. A survey was conducted to collect data from teachers. The population of the study comprised teachers teaching in regular schools in 10 divisions of Punjab. 190 teachers(male=56, female=136)were selected for the study from 20 districts, and 2 schools from each division were randomly selected. A self-administered questionnaire comprised of 8 units was used as a research instrument. Data was analyzed through SPSS IBM 22. It was decided to use both descriptive and inferential statistics. The findings of the study revealed the needs of general education teachers in terms of awareness, classroom management, curriculum adaptation, instructional methodology, and materials, and assessment procedures adaptation to accommodate SWVI in inclusive settings. No difference was revealed in the needs of teachers based on gender or locality. Based on the findings, teachers' training, awareness, and empowerment to educate students with visual impairment in inclusive settings is recommended by the researchers.